Cementing material as well as preparation method and application thereof
By using alternative materials such as recycled cement, carbonized waste incineration fly ash and dehydrated phosphogypsum, low-carbon gelling materials are prepared, which solves the problem of high carbon emissions of LC3 and achieves waste reuse and efficient compressive strength.
Patent Information
- Application Number
- CN202411557738.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-07
AI Technical Summary
LC3 has high carbon emissions caused by cement preparation and limestone mining.
By using alternative materials such as recycled cement, carbonized waste incineration fly ash and dehydrated phosphogypsum, a low-carbon gelling material is prepared to reduce carbon emissions and achieve waste reuse.
The carbon emissions are reduced, and the waste reuse of concrete waste powder and waste incineration fly ash is realized. The gelled material is hydrated and hardened at a fast speed, has sufficient compressive strength, and can replace LC3.
Smart Images

Figure CN119390371A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of cementitious materials, and in particular to a cementitious material and a preparation method and application thereof. Background Art
[0002] Calcined limestone clay cement (LC3) is a new type of low-carbon cementitious material system that has attracted much attention. It effectively improves the economic and ecological benefits of cementitious materials by compounding calcined clay, limestone powder and gypsum and replacing part of cement clinker. The most commonly used LC3 system is LC3-50, which includes 50% cement, 30% calcined clay, 15% limestone and 5% gypsum. In the LC3 system, aluminum-rich calcined clay can react with Ca(OH)2 produced by cement hydration to form CASH gel, which improves the mechanical properties of the system. Due to its excellent properties and mechanical performance, LC3 is considered to be a substitute for cement or cementitious materials in concrete.
[0003] However, LC3 has the problem of high carbon emissions caused by cement preparation and limestone mining. Therefore, it is very necessary to develop a low-carbon cementitious material to replace LC3. Summary of the invention
[0004] Based on the above-mentioned deficiencies of the prior art, the purpose of the present invention is to provide a cementitious material and a preparation method and application thereof, aiming to solve the problem of high carbon emissions caused by cement preparation and limestone mining in LC3.
[0005] The technical solution of the present invention is as follows:
[0006] The first aspect of the present invention provides a gelling material, wherein the gelling material comprises the following components in parts by mass:
[0007] 0-40 parts of the first component, 10-50 parts of recycled cement, 30 parts of the second component, 15 parts of carbonized waste incineration fly ash and 5 parts of dehydrated phosphogypsum;
[0008] The first component includes cement and / or concrete waste powder; the second component includes calcined clay and / or calcined engineering slag;
[0009] The recycled cement is obtained by mechanically grinding waste concrete powder, or the recycled cement is obtained by mechanically grinding and heat treating waste concrete powder;
[0010] The carbonized waste incineration fly ash is obtained by carbonizing the waste incineration fly ash.
[0011] Optionally, the cement in the first component is ordinary Portland cement.
[0012] The second aspect of the present invention provides a method for preparing the gelling material as described above, which comprises the following steps:
[0013] The waste concrete powder is mechanically ground to obtain recycled cement, or the waste concrete powder is mechanically ground and heat treated to obtain recycled cement;
[0014] Carbonizing the waste incineration fly ash to obtain carbonized waste incineration fly ash;
[0015] The cementitious material is obtained by mixing 0-40 parts of the first component, 10-50 parts of recycled cement, 30 parts of the second component, 15 parts of carbonized waste incineration fly ash and 5 parts of dehydrated phosphogypsum, in parts by mass;
[0016] The first component includes cement and / or concrete waste powder; the second component includes calcined clay and / or calcined engineering slag.
[0017] Optionally, the step of obtaining recycled cement by mechanically grinding waste concrete powder specifically comprises:
[0018] The waste concrete powder and steel balls are placed in a ball mill, the mass ratio of the steel balls to the waste concrete powder is (20-25):1, and then ball milled at a rotation speed of 120 rpm for 30-60 minutes, and then passed through a 0.075-0.3 mm sieve to obtain the recycled cement.
[0019] Optionally, the step of obtaining recycled cement by mechanically grinding and heat treating waste concrete powder specifically comprises:
[0020] The waste concrete powder and steel balls are placed in a ball mill, the mass ratio of the steel balls to the waste concrete powder is (20-25):1, and then ball milled at a rotation speed of 120rpm for 30-60min, passed through a 0.075-0.3mm sieve, and then heat treated at a temperature of 600°C for 2h to obtain the recycled cement.
[0021] Optionally, waste concrete powder, steel balls and triethanolamine are placed in a ball mill, and the mass of the triethanolamine is one thousandth of the mass of the waste concrete powder.
[0022] Optionally, the step of obtaining carbonized waste incineration fly ash after carbonizing the waste incineration fly ash specifically comprises:
[0023] The waste incineration fly ash is placed in an environment with a relative humidity of 65±5%, a CO2 volume concentration of 20%, and a temperature of 20° C. for carbonization to obtain carbonized waste incineration fly ash.
[0024] Optionally, the step of obtaining carbonized waste incineration fly ash after carbonizing the waste incineration fly ash specifically comprises:
[0025] The waste incineration fly ash is placed in a carbonization box at a relative humidity of 65±5%, a CO2 volume concentration of 20%, and a temperature of 20°C for carbonization for one week, and then baked at a temperature of 105°C for 2-3 days. After passing through a 150-200 mesh sieve, carbonized waste incineration fly ash is obtained.
[0026] Optionally, the method for preparing the dehydrated phosphogypsum comprises the following steps:
[0027] The phosphogypsum is calcined at a temperature of 150-200° C. for 2 hours to obtain the dehydrated phosphogypsum.
[0028] The third aspect of the present invention provides the use of the above-mentioned cementitious material of the present invention in replacing limestone calcined clay cement in the field of construction.
[0029] Beneficial effects: The cementitious material provided by the present invention does not contain limestone with a high carbon emission, does not contain or contains a small amount of cement with a high carbon emission, thereby reducing carbon emissions. At the same time, it consumes waste such as concrete waste powder and waste incineration fly ash, realizes the waste recycling of concrete waste powder and waste incineration fly ash, and further reduces carbon emissions. In addition, carbonized waste incineration fly ash can also fix a portion of carbon dioxide and solidify the leaching of heavy metals such as Pb in the natural environment. Therefore, the cementitious material provided by the present invention is a low-carbon cementitious material and has a low cost. The cementitious material provided by the present invention has a fast hydration and hardening speed and has sufficient compressive strength. It can be used instead of LC3 and has lower carbon emissions than LC3. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a graph showing the compressive strength test results of the cementitious material test blocks in Examples 1 to 15 and the cement material test blocks in Comparative Examples 1 and 2.
[0031] Figure 2 This is a graph showing the compressive strength test results of the cementitious material test blocks in Examples 16 to 19. DETAILED DESCRIPTION
[0032] The present invention provides a gelling material and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0034] The embodiment of the present invention provides a cementitious material (also known as a low-carbon cementitious material or a low-carbon cement material), wherein the cementitious material comprises the following components in parts by mass:
[0035] 0-40 parts of the first component, 10-50 parts of recycled cement, 30 parts of the second component, 15 parts of carbonized waste incineration fly ash and 5 parts of dehydrated phosphogypsum;
[0036] The first component includes cement and / or concrete waste powder; the second component includes calcined clay and / or calcined engineering slag;
[0037] The recycled cement is obtained by mechanically grinding waste concrete powder, or the recycled cement is obtained by mechanically grinding and heat treating waste concrete powder;
[0038] The carbonized waste incineration fly ash is obtained by carbonizing the waste incineration fly ash.
[0039] LC3 contains cement and limestone with high carbon emissions, while the cementitious material provided by the present invention does not contain limestone with high carbon emissions, and does not contain or contains a small amount of cement with high carbon emissions, thereby reducing carbon emissions. At the same time, it consumes waste such as concrete waste powder and waste incineration fly ash, thereby realizing the waste recycling of concrete waste powder and waste incineration fly ash, and further reducing carbon emissions. In addition, carbonized waste incineration fly ash can also fix a portion of carbon dioxide and solidify the leaching of heavy metals such as Pb in the natural environment. Therefore, the cementitious material provided by the present invention is a low-carbon cementitious material with low cost. The cementitious material provided by the present invention has a fast hydration and hardening speed, and has sufficient compressive strength. It can be used instead of LC3 and has lower carbon emissions than LC3 (the carbon emissions of the cementitious material provided by the present invention can be 50% of that of LC3).
[0040] Among them, the carbonization treatment of waste incineration fly ash can increase the calcium carbonate content therein, thereby providing more nucleation sites for the hydration reaction of the cementitious material, thereby promoting the hydration reaction of the cementitious material. Specifically, because the waste incineration fly ash is collected in the flue gas collection system of the waste incineration plant, after the waste incineration fly ash is collected by the flue gas collection system of the waste incineration plant (or waste incinerator), a calcium oxide solution will be sprayed to solidify the heavy metals therein, so the waste incineration fly ash will contain many alkaline substances, including calcium oxide, calcium hydroxide and CaClOH, etc. After the waste incineration fly ash is carbonized, the calcium oxide, calcium hydroxide and CaClOH react with carbon dioxide to form calcium carbonate, so the waste incineration fly ash can be carbonized to increase the calcium carbonate content therein. In addition, the carbonization treatment of waste incineration fly ash can also solidify the leaching of heavy metals such as Pb in the natural environment.
[0041] Mechanical grinding of waste concrete powder can change its physical properties and crystal structure. Specifically, mechanical grinding of waste concrete powder can reduce its particle size and destroy the crystal structure, so that the crystal has rehydration characteristics and promotes its hydration reaction in cementitious materials. The physical and chemical structure of waste concrete powder after mechanical grinding can be changed by heat treatment (i.e., heat activation treatment), the microstructure can be optimized, and the inactive CSH therein can be transformed into dehydrated CSH that can be hydrated, forming a porous amorphous structure, promoting and accelerating the hydration and hardening of cementitious materials, and at the same time producing calcium hydroxide to stimulate the volcanic ash reaction of calcined clay to generate high-strength CASH gel, thereby increasing the compressive strength of cementitious materials. Therefore, the recycled cement obtained by mechanical grinding and heat activation of waste concrete powder has similar hydration products and better mechanical properties as cement.
[0042] The use of dehydrated phosphogypsum can delay the flash setting of recycled cement and improve its working performance.
[0043] In some embodiments, the cement in the first component is ordinary Portland cement.
[0044] The present invention also provides a method for preparing the gelling material according to the present invention, which comprises the following steps:
[0045] S1. Grinding concrete waste powder mechanically to obtain recycled cement, or grinding concrete waste powder mechanically and heat treating to obtain recycled cement;
[0046] S2, subjecting the waste incineration fly ash to carbonization treatment to obtain carbonized waste incineration fly ash;
[0047] S3. By mixing, by mass, 0-40 parts of the first component, 10-50 parts of recycled cement, 30 parts of the second component, 15 parts of carbonized waste incineration fly ash and 5 parts of dehydrated phosphogypsum, the cementitious material is obtained; the first component includes cement and / or concrete waste powder; the second component includes calcined clay and / or calcined engineering slag.
[0048] The cementitious material provided by the present invention does not contain limestone with a high carbon emission, does not contain or contains a small amount of cement with a high carbon emission, thereby reducing carbon emissions. At the same time, it consumes waste such as concrete waste powder and waste incineration fly ash, realizes the waste recycling of concrete waste powder and waste incineration fly ash, and further reduces carbon emissions. In addition, carbonized waste incineration fly ash can also fix a portion of carbon dioxide and solidify the leaching of heavy metals such as Pb in the natural environment. Therefore, the cementitious material provided by the present invention is a low-carbon cementitious material. The cementitious material provided by the present invention has a fast hydration and hardening speed, and has sufficient compressive strength, can be used instead of LC3, and has lower carbon emissions compared to LC3.
[0049] In step S1, in some embodiments, the step of obtaining recycled cement by mechanically grinding the waste concrete powder specifically includes:
[0050] The waste concrete powder and steel balls are placed in a ball mill, the mass ratio of the steel balls to the waste concrete powder is (20-25):1, and then ball milled at a rotation speed of 120 rpm for 30-60 minutes, and then passed through a 0.075-0.3 mm sieve to obtain the recycled cement.
[0051] In some embodiments, the step of obtaining recycled cement by mechanically grinding and heat treating waste concrete powder specifically comprises:
[0052] The waste concrete powder and steel balls are placed in a ball mill with a mass ratio of steel balls to waste concrete powder of (20-25):1, and then ball-milled at a rotation speed of 120 rpm for 30-60 min, passed through a 0.075-0.3 mm sieve, and then heat-treated at a temperature of 600° C. for 2 h to obtain the recycled cement (i.e., heat-activated recycled cement).
[0053] For example, the mass ratio of steel balls to waste concrete powder can be 20:1, 21:1, 22:1, 23:1, 24:1 or 25:1, etc. The ball milling time can be 30 min, 40 min, 50 min or 60 min, etc. The powder can be sieved with a 0.075 mm, 0.1 mm, 0.2 mm or 0.3 mm screen.
[0054] Mechanical grinding of concrete waste powder can reduce its particle size and destroy its crystal structure, so that the crystal has rehydration characteristics and promotes its hydration reaction in cementitious materials. The physical and chemical structure of concrete waste powder after mechanical grinding can be changed by heat treatment (i.e., heat activation treatment), and the microstructure can be optimized. The original calcium vanadium, monosulfate and calcium hydroxide in the concrete waste powder can be decomposed, and the inactive CSH therein can be converted into dehydrated CSH that can be hydrated, forming a porous amorphous structure, promoting the hydration of cementitious materials and accelerating their hardening. At the same time, calcium hydroxide is produced to stimulate the volcanic ash reaction of calcined clay to generate high-strength CASH gel, thereby increasing the compressive strength of cementitious materials. Therefore, the recycled cement (i.e., heat-activated recycled cement) obtained by mechanical grinding and heat activation of concrete waste powder has similar hydration products and better mechanical properties as cement.
[0055] In some embodiments, waste concrete powder, steel balls and triethanolamine are placed in a ball mill, and the mass of the triethanolamine is one thousandth of the mass of the waste concrete powder.
[0056] Triethanolamine can be used as a grinding aid to further reduce the particle size of concrete waste powder, and it can also accelerate the hydration reaction of cementitious materials.
[0057] In step S2, in some embodiments, the step of obtaining carbonized waste incineration fly ash after carbonizing the waste incineration fly ash specifically includes:
[0058] The waste incineration fly ash is placed in an environment with a relative humidity of 65±5%, a CO2 volume concentration of 20%, and a temperature of 20° C. for carbonization to obtain carbonized waste incineration fly ash.
[0059] In some embodiments, the step of subjecting the waste incineration fly ash to carbonization to obtain carbonized waste incineration fly ash specifically comprises:
[0060] The waste incineration fly ash is placed in a carbonization box with a relative humidity of 65±5%, a CO2 volume concentration of 20%, and a temperature of 20°C for carbonization for one week (7 days), and then baked at a temperature of 105°C for 2 to 3 days (for example, 2 days or 3 days, etc.), and sieved through 150 to 200 meshes (where 150 mesh corresponds to 0.15 mm, and 200 mesh corresponds to 0.075 mm) to obtain carbonized waste incineration fly ash.
[0061] Waste incineration fly ash contains many alkaline substances, including calcium oxide, calcium hydroxide and CaClOH. After the waste incineration fly ash is carbonized, the calcium oxide, calcium hydroxide and CaClOH in the fly ash react with carbon dioxide to form calcium carbonate, which can increase the calcium carbonate content and provide more nucleation sites for the hydration reaction of the cementitious material, thereby promoting the hydration reaction of the cementitious material.
[0062] In some embodiments, the method for preparing dehydrated phosphogypsum comprises the following steps:
[0063] The phosphogypsum is calcined at a temperature of 150-200° C. (for example, 150° C., 160° C., 170° C., 180° C., 190° C. or 200° C.) for 2 hours to obtain the dehydrated phosphogypsum.
[0064] The embodiment of the present invention also provides the use of the cementitious material described above in the embodiment of the present invention in the field of construction to replace limestone calcined clay cement.
[0065] The cementitious material provided by the present invention has fast hydration and hardening speeds and sufficient compressive strength, can be used in place of LC3, and has lower carbon emissions than LC3.
[0066] The present invention will be further described below by means of specific examples.
[0067] In the following examples and comparative examples, the method for preparing carbonized waste incineration fly ash comprises the following steps:
[0068] The waste incineration fly ash (IFA for short, from the waste incineration plant in Foshan, Guangdong, without any detoxification treatment before use) was sieved through a 150-mesh sieve. Then 1 kg of the sieved IFA was placed in a 60cm×40cm×5cm iron plate, covered with plastic wrap and 100 small holes were evenly pierced, and placed in a carbonization box (relative humidity: 65±5%, CO2 concentration: 20%, temperature: 20°C) for one week (7 days) of carbonization, and turned over on the 1st, 3rd and 5th days respectively. After the carbonization is completed, it was placed in a 105°C drying oven for 2 days, and after drying, it was sieved through a 150-mesh sieve again to obtain carbonized IFA (denoted as CIFA).
[0069] The method for preparing recycled cement comprises the following steps:
[0070] The waste concrete powder was placed in a ball mill and steel balls were added (the mass ratio of steel balls to waste concrete powder was 25:1). The ball mill was milled at a speed of 120 rpm for 60 min and then passed through a 0.3 mm sieve to obtain recycled cement, which was recorded as M-RC.
[0071] The waste concrete powder was placed in a ball mill, and steel balls (the mass ratio of steel balls to waste concrete powder was 25:1) and triethanolamine (triethanolamine was one thousandth of the mass of waste concrete powder) were added, and the ball milling was carried out at a rotation speed of 120 rpm for 60 minutes, and then passed through a 0.3 mm sieve to obtain recycled cement, which was recorded as C-RC.
[0072] 200 g of M-RC was put into a ceramic crucible with an inner diameter of 100 mm and a height of 127 mm, and then the whole was placed in a muffle furnace and heated to 600 °C at a heating rate of 10 °C / min, kept warm for 2 h, and then naturally cooled to 200 °C. The crucible was taken out and cooled in a natural state to obtain recycled cement (also known as heat-activated recycled cement), which was recorded as T-RC.
[0073] The preparation method of dehydrated phosphogypsum comprises the following steps:
[0074] The phosphogypsum was placed in a muffle furnace, heated to 150°C at a heating rate of 10°C / min, and calcined at 150°C for 2 hours to obtain dehydrated phosphogypsum.
[0075] The cement used in the following examples and comparative examples is PO 42.5 ordinary Portland cement, denoted as OPC.
[0076] Table 1. Proportion of each component in the examples and comparative examples (wt%, mass percentage)
[0077]
[0078]
[0079] Example 1
[0080] This embodiment provides a cementitious material, the components and proportions of the cementitious material are shown in Table 1 as the components and proportions of Example 1, that is, the cementitious material consists of 40wt% of OPC, 10wt% of M-RC, 30wt% of calcined clay, 15wt% of CIFA and 5wt% of dehydrated phosphogypsum.
[0081] The cementitious material test blocks were prepared using cementitious materials and the compressive strength was tested:
[0082] After weighing the components in the proportion of Example 1 in Table 1, place them in a stirring pot, first stir the dry material slowly (60rpm) for 120s, then slowly add water to make the water-cement ratio (W / B, that is, the ratio of water to cement or the ratio of water to concrete waste powder) 0.55 (the water-cement ratio in the following examples and comparative examples is 0.55), stir slowly (60rpm) for 60s after adding water, and then stir quickly (120rpm) for 60s. Then, pour it into a mold with a size of 20mm×20mm×20mm, and cover it with a plastic film. Remove the mold after hardening for 1 day. The obtained test block is sent to a standard curing room (relative humidity of 95±5%, temperature of 20±2℃) for curing to the age, and the obtained cementitious material test block is recorded as M-10. In addition, compressive strength tests are carried out after curing for 3 days, 7 days and 28 days respectively.
[0083] Example 2
[0084] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 2.
[0085] The cementitious material was used to prepare cementitious material test blocks, and the compressive strength test was performed on the cementitious material test blocks. The only difference from Example 1 was that the components were weighed according to the proportions of Example 2 in Table 1, and the obtained cementitious material test blocks were recorded as M-20. Similarly, the compressive strength test was performed after curing for 3 days, 7 days and 28 days respectively.
[0086] Example 3
[0087] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 3.
[0088] The cementitious material was used to prepare cementitious material test blocks, and the compressive strength test was performed on the cementitious material test blocks. The only difference from Example 1 was that the components were weighed according to the proportions of Example 3 in Table 1, and the obtained cementitious material test blocks were recorded as M-30. Similarly, the compressive strength test was performed after curing for 3 days, 7 days and 28 days respectively.
[0089] Example 4
[0090] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 4.
[0091] The cementitious material was used to prepare cementitious material test blocks, and the compressive strength test was performed on the cementitious material test blocks. The only difference from Example 1 was that the components were weighed according to the proportions of Example 4 in Table 1, and the obtained cementitious material test blocks were recorded as M-40. Similarly, the compressive strength test was performed after curing for 3 days, 7 days and 28 days respectively.
[0092] Example 5
[0093] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 5.
[0094] The cementitious material was used to prepare cementitious material test blocks, and the compressive strength test was performed on the cementitious material test blocks. The only difference from Example 1 was that the components were weighed according to the proportions of Example 5 in Table 1, and the obtained cementitious material test blocks were recorded as M-50. Similarly, the compressive strength test was performed after curing for 3 days, 7 days and 28 days respectively.
[0095] Example 6
[0096] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 6.
[0097] Cementitious material test blocks were prepared using cementitious materials and subjected to compressive strength tests. The only difference from Example 1 was that the components were weighed according to the proportions of Example 6 in Table 1, and the obtained cementitious material test blocks were recorded as C-10. Similarly, compressive strength tests were performed after curing for 3 days, 7 days, and 28 days, respectively.
[0098] Example 7
[0099] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 7.
[0100] Cementitious material test blocks were prepared using cementitious materials and subjected to compressive strength tests. The only difference from Example 1 was that the components were weighed according to the proportions of Example 7 in Table 1, and the obtained cementitious material test blocks were recorded as C-20. Similarly, compressive strength tests were performed after curing for 3 days, 7 days, and 28 days, respectively.
[0101] Example 8
[0102] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 8.
[0103] Cementitious material test blocks were prepared using the cementitious material and subjected to compressive strength tests. The only difference from Example 1 was that the components were weighed according to the proportions of Example 8 in Table 1, and the obtained cementitious material test blocks were recorded as C-30. Similarly, compressive strength tests were performed after curing for 3 days, 7 days, and 28 days, respectively.
[0104] Example 9
[0105] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 9.
[0106] Cementitious material test blocks were prepared using cementitious materials and subjected to compressive strength tests. The only difference from Example 1 was that the components were weighed according to the proportions of Example 9 in Table 1, and the obtained cementitious material test blocks were recorded as C-40. Similarly, compressive strength tests were performed after curing for 3 days, 7 days, and 28 days, respectively.
[0107] Example 10
[0108] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 10.
[0109] Cementitious material test blocks were prepared using cementitious material and subjected to compressive strength tests. The only difference from Example 1 was that the components were weighed according to the proportions of Example 10 in Table 1, and the obtained cementitious material test blocks were recorded as C-50. Similarly, compressive strength tests were performed after curing for 3 days, 7 days, and 28 days, respectively.
[0110] Embodiment 11
[0111] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 11.
[0112] The cementitious material was used to prepare cementitious material test blocks, and the compressive strength test was performed on the cementitious material test blocks. The only difference from Example 1 was that the components were weighed according to the proportions of Example 11 in Table 1, and the obtained cementitious material test blocks were recorded as T-10. Similarly, the compressive strength test was performed after curing for 3 days, 7 days and 28 days respectively.
[0113] Example 12
[0114] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 12.
[0115] The cementitious material was used to prepare cementitious material test blocks, and the compressive strength test was performed on the cementitious material test blocks. The only difference from Example 1 was that the components were weighed according to the proportions of Example 12 in Table 1, and the obtained cementitious material test blocks were recorded as T-20. Similarly, the compressive strength test was performed after curing for 3 days, 7 days and 28 days respectively.
[0116] Example 13
[0117] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 13.
[0118] The cementitious material was used to prepare cementitious material test blocks, and the compressive strength test was performed on the cementitious material test blocks. The only difference from Example 1 was that the components were weighed according to the proportions of Example 13 in Table 1, and the obtained cementitious material test blocks were recorded as T-30. Similarly, the compressive strength test was performed after curing for 3 days, 7 days and 28 days respectively.
[0119] Embodiment 14
[0120] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 14.
[0121] Cementitious material test blocks were prepared using cementitious material and subjected to compressive strength tests. The only difference from Example 1 was that the components were weighed according to the proportions of Example 14 in Table 1, and the obtained cementitious material test blocks were recorded as T-40. Similarly, compressive strength tests were performed after curing for 3 days, 7 days, and 28 days, respectively.
[0122] Embodiment 15
[0123] This embodiment provides a cementitious material, which is different from Embodiment 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 15.
[0124] The cementitious material was used to prepare cementitious material test blocks, and the compressive strength test was performed on the cementitious material test blocks. The difference from Example 1 was that the components were weighed according to the proportions of Example 15 in Table 1, and the obtained cementitious material test blocks were recorded as T-50. Similarly, the compressive strength test was performed after curing for 3 days, 7 days and 28 days respectively.
[0125] Comparative Example 1
[0126] This comparative example provides a cement material, which is different from Example 1 only in that the components and proportions of the cement material are shown in Table 1 for the components and proportions of Comparative Example 1.
[0127] Cement material test blocks were prepared using cement material and subjected to compressive strength tests. The only difference from Example 1 was that the components were weighed according to the proportions of Comparative Example 1 in Table 1, and the obtained cement material test blocks were recorded as LC3. Similarly, compressive strength tests were performed after curing for 3 days, 7 days, and 28 days, respectively.
[0128] Comparative Example 2
[0129] This comparative example provides a cement material, which is different from Example 1 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Comparative Example 2.
[0130] Cement material test blocks were prepared using cement material and subjected to compressive strength tests. The only difference from Example 1 was that the components were weighed according to the proportions of Comparative Example 2 in Table 1, and the obtained cement material test blocks were recorded as CDW0. Similarly, compressive strength tests were performed after curing for 3 days, 7 days, and 28 days, respectively.
[0131] The compressive strength test results of the cementitious material test blocks in Examples 1 to 15 and the cement material test blocks in Comparative Examples 1 and 2 are as follows: Figure 1 As shown, it can be seen that the cementitious material test blocks in Examples 1 to 15 all have good compressive strength, especially T-10 to T-50 in Examples 11 to 15 have higher compressive strength, even higher than the current limestone calcined clay cement (LC3), especially T-50 has a usable compressive strength without using cement at all. After 3 days of curing, it reached a compressive strength of 9.2 MPa, and after 28 days of curing, it reached a compressive strength of 23.1 MPa.
[0132] Example 16
[0133] This embodiment provides a cementitious material, which is different from Embodiment 11 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 16 (ie, the OPC in Embodiment 11 is replaced by concrete waste powder).
[0134] Cementitious material test blocks were prepared using cementitious materials and subjected to compressive strength tests. The only difference from Example 11 was that the components were weighed according to the proportions of Example 16 in Table 1, and the obtained cementitious material test blocks were recorded as T-10-1. Similarly, compressive strength tests were performed after curing for 3 days, 7 days, and 28 days, respectively.
[0135] Embodiment 17
[0136] This embodiment provides a cementitious material, which is different from Embodiment 12 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 17 (ie, the OPC in Embodiment 12 is replaced by waste concrete powder).
[0137] The cementitious material was used to prepare cementitious material test blocks, and the compressive strength test was performed on the cementitious material test blocks. The only difference from Example 12 was that the components were weighed according to the proportions of Example 17 in Table 1, and the obtained cementitious material test blocks were recorded as T-20-1. Similarly, the compressive strength test was performed after curing for 3 days, 7 days and 28 days respectively.
[0138] Embodiment 18
[0139] This embodiment provides a cementitious material, which is different from Embodiment 13 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 18 (ie, the OPC in Embodiment 13 is replaced by concrete waste powder).
[0140] Cementitious material test blocks were prepared using cementitious material and subjected to compressive strength tests. The only difference from Example 13 was that the components were weighed according to the proportions of Example 18 in Table 1, and the obtained cementitious material test blocks were recorded as T-30-1. Similarly, compressive strength tests were performed after curing for 3 days, 7 days, and 28 days, respectively.
[0141] Embodiment 19
[0142] This embodiment provides a cementitious material, which is different from Embodiment 14 only in that the components and proportions of the cementitious material are shown in Table 1 for the components and proportions of Embodiment 19 (ie, the OPC in Embodiment 14 is replaced by concrete waste powder).
[0143] The cementitious material was used to prepare cementitious material test blocks, and the compressive strength test was performed on the cementitious material test blocks. The only difference from Example 14 was that the components were weighed according to the proportions of Example 19 in Table 1, and the obtained cementitious material test blocks were recorded as T-40-1. Similarly, the compressive strength test was performed after curing for 3 days, 7 days and 28 days respectively.
[0144] The compressive strength test results of the cementitious material test blocks in Examples 16 to 19 are as follows: Figure 2 As shown, it can be seen that the cementitious materials in Examples 16 to 19 also have high compressive strength and can be used instead of LC3.
[0145] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A gelling material, characterized in that: The gelling material comprises the following components by mass: 0-40 parts of the first component, 10-50 parts of recycled cement, 30 parts of the second component, 15 parts of carbonized waste incineration fly ash and 5 parts of dehydrated phosphogypsum; The first component includes cement and / or concrete waste powder; the second component includes calcined clay and / or calcined engineering slag; The recycled cement is obtained by mechanically grinding waste concrete powder, or the recycled cement is obtained by mechanically grinding and heat treating waste concrete powder; The carbonized waste incineration fly ash is obtained by subjecting waste incineration fly ash to carbonization treatment.
2. The cementitious material according to claim 1, characterized in that The cement in the first component is ordinary Portland cement.
3. A method for preparing the gelling material according to claim 1, characterized in that: The steps include: The waste concrete powder is mechanically ground to obtain recycled cement, or the waste concrete powder is mechanically ground and heat treated to obtain recycled cement; Carbonizing the waste incineration fly ash to obtain carbonized waste incineration fly ash; By weight, 0-40 parts of the first component, 10-50 parts of recycled cement, 30 parts of the second component, 15 parts of carbonized waste incineration fly ash and 5 parts of dehydrated phosphogypsum are mixed to obtain the cementitious material; The first component includes cement and / or concrete waste powder; the second component includes calcined clay and / or calcined engineering slag.
4. The preparation method according to claim 3, characterized in that: The step of obtaining recycled cement by mechanically grinding waste concrete powder specifically comprises: The waste concrete powder and steel balls are placed in a ball mill, the mass ratio of the steel balls to the waste concrete powder is (20-25):1, and then ball milled at a rotation speed of 120 rpm for 30-60 minutes, and then passed through a 0.075-0.3 mm sieve to obtain the recycled cement.
5. The preparation method according to claim 3, characterized in that: The step of obtaining recycled cement by mechanically grinding and heat treating the waste concrete powder specifically comprises: The waste concrete powder and steel balls are placed in a ball mill, the mass ratio of the steel balls to the waste concrete powder is (20-25):1, and then ball milled at a rotation speed of 120rpm for 30-60min, passed through a 0.075-0.3mm sieve, and then heat treated at a temperature of 600°C for 2h to obtain the recycled cement.
6. The preparation method according to claim 4 or 5, characterized in that: Concrete waste powder, steel balls and triethanolamine are placed in a ball mill, and the mass of the triethanolamine is one thousandth of the mass of the concrete waste powder.
7. The preparation method according to claim 3, characterized in that: The step of obtaining carbonized waste incineration fly ash after carbonizing the waste incineration fly ash specifically comprises: The waste incineration fly ash is placed in an environment with a relative humidity of 65±5%, a CO2 volume concentration of 20%, and a temperature of 20° C. for carbonization to obtain carbonized waste incineration fly ash.
8. The preparation method according to claim 7, characterized in that: The step of obtaining carbonized waste incineration fly ash after carbonizing the waste incineration fly ash specifically comprises: The waste incineration fly ash is placed in a carbonization box at a relative humidity of 65±5%, a CO2 volume concentration of 20%, and a temperature of 20°C for carbonization for one week, and then baked at a temperature of 105°C for 2-3 days. After passing through a 150-200 mesh sieve, carbonized waste incineration fly ash is obtained.
9. The preparation method according to claim 3, characterized in that: The preparation method of the dehydrated phosphogypsum comprises the following steps: The phosphogypsum is calcined at a temperature of 150-200° C. for 2 hours to obtain the dehydrated phosphogypsum.
10. Use of the cementitious material according to any one of claims 1 to 2 in the construction field as a substitute for limestone calcined clay cement.
Citation Information
Patent Citations
High-property concrete containing active regenerative micropowder and preparation method thereof
CN109320162A